1995
DOI: 10.1093/jac/36.suppl_a.85
|View full text |Cite
|
Sign up to set email alerts
|

A randomised comparison of meropenem with cefotaxime or ceftriaxone for the treatment of bacterial meningitis in adults

Abstract: Third-generation cephalosporins are presently the agents of choice for the empirical antimicrobial therapy of bacterial meningitis. However, a number of factors associated with these agents, namely the development of resistance by pneumococci, limited activity against some Enterobacteriaceae and Pseudomonas spp., and the possible adverse effects of their bacteriolytic mode of action, indicate that newer classes of antimicrobial agents be evaluated for the treatment of bacterial meningitis. Meropenem is a carba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(45 citation statements)
references
References 0 publications
1
39
0
3
Order By: Relevance
“…Fuchs et al [28] reported that among 342 clinical isolates of S. pneumoniae, meropenem MICs for penicillin-resistant strains were 0.25-4.0 mg/l, while those of penicillin-susceptible strains were X0.008-0.06 mg/l. Meropenem has already been tested for the treatment of meningitis in both adults and children, but only a small amount of data for patients infected by penicillin-and cephalosporin-resistant S. pneumoniae is available to date [29][30][31]. More clinical data are required before it can be recommended as an effective antimicrobial agent for such cases.…”
Section: Discussionmentioning
confidence: 99%
“…Fuchs et al [28] reported that among 342 clinical isolates of S. pneumoniae, meropenem MICs for penicillin-resistant strains were 0.25-4.0 mg/l, while those of penicillin-susceptible strains were X0.008-0.06 mg/l. Meropenem has already been tested for the treatment of meningitis in both adults and children, but only a small amount of data for patients infected by penicillin-and cephalosporin-resistant S. pneumoniae is available to date [29][30][31]. More clinical data are required before it can be recommended as an effective antimicrobial agent for such cases.…”
Section: Discussionmentioning
confidence: 99%
“…Meropenem has been shown to be effective in several animal models [13]. In clinical trials, it has been used successfully to treat pneumonia [26,29], meningitis [11,21,37], intra-abdominal infections [16,17,20], soft tissue infections [22,30], bacteremia [29], and urinary tract infections [8,29].…”
Section: Discussionmentioning
confidence: 99%
“…Worth mentioning is that vancomycin use has become the focus of considerable attention in recent years due to the emergence of vancomycin-resistant enterococci (VRE) and the recent description of Staphylococcus aureus with intermediate resistance to vancomycin (VISA). Importantly, previous vancomycin therapy is a risk factor for the development of VRE infection [17,20,21]. In view of these concerns our observation that meropenem may be associated with a lesser use of vancomycin suggests that meropenem has advantages over ceftazidime in this setting.…”
Section: Discussionmentioning
confidence: 91%
“…Meropenem, unlike imipenem/cilastatin, is relatively stable to renal dehydropeptidase-I (DHP-I) and therefore does not need to be co-administered with a DHP-I inhibitor such as cilastatin. Meropenem may be a more acceptable alternative to imipenem/cilastatin because it has shown a low incidence of nausea and vomiting and is well tolerated by the central nervous system (CNS) [15,16,17], even in neutropenic patients [7,18].…”
Section: Introductionmentioning
confidence: 99%